Efeito antibacteriano de tecidos têxteis revestidos por prata através da técnica de deposição por plasma - Feitor, Michele Cequeira (2010)
In this study, it has been investigated the influence of silver film deposition onto 100% polyester woven and non-woven, on the survival of Escherichia coli and Staphylococcus aureus in contact with these surfaces. The treatment was performedin a chamber containing the working gas at low pressure (~ 10-2 mbar). Some process parameters such as as voltage: 470 V; pressure: 10-2 mbar; current : 0.40 A and gas flow: 6 and 10 cm3/min were kept constant. For the treatments with purêargon plasma using a flow of 6 and 10 cm3/min, different treatment times were evaluated, such as, 10 , 20, 30, 40, 50 and 60 minutes. Contact angle (sessile drop), measurements were used to determine the surface tension of the treated fabrics and its influence on the bacteria grow as weel as the possibilities of a biofilm formation. The formation of a silver film, as well as the amount of this element was verified byEDX technique. The topography was observed through scanning electron microscopy (SEM) to determine the size of silver grains formed on the surfaces of the fabric and assess homogeneity of treatment. The X-ray diffraction (XRD) was used to analyze the structure of silver film deposition. The woven fabric treatments enabled the formation of silver particulate films with particle size larger than the non-woven fabrics. With respect to bacterial growth, all fabrics were shown to be bactericidal for Staphylococcus aureus (S. aureus), while for the Escherichia coli (E. coli), the best results were found for the non-woven fabric (TNT) treated with a flow of 10 cm3/min to both bacteria